Pengaruh Kepemimpinan Dan Pengembangan Karir Terhadap Komitmen Karyawan PT Khalifa International Business Di Jakarta - M. Irfan Nawawi; Aryanda Aryanda (Postgraduate of Jayabaya University, 2015)
The purposed of this research was to identified the effect of leadership and career development partially and simultaneously on employee commitment PT Khalifa International Business in Jakarta. Research conducted on 21 employees of PT Khalifa International Business, data processing using analysis Regression. It is showed positive effect leadership and career development on employee commitment partially and simultaneously. With this research explicitly illustrated and analyzed the effect of leadership and career development on employee commitment including how the relationship between variables.